Correction: Protein-losing enteropathy in patients with Fontan circulation: is it triggered by infection? - Lenz, Dominik (BioMed Central, 2003)
A correction to Protein-losing enteropathy in patients with Fontan circulation: is it triggered by infection? by Dominik Lenz, Jorg Hambsch, Peter Schneider, Hans-Jungen Hausler, Ursula Sauer, John Hess and Attila Tarnok. In the original version of this article [1], the grant sponsor of this study was listed incorrectly. The Acknowledgements section should have read as follows: 'JH and DL contributed equally to this manuscript. This work was supported by the Maximillian research award 1997 of the Herzkind e.V. and by a research grant (DL) of the Herzkind e.V.'